Upaya Pembentukan Karakter Remaja di Panti Asuhan Yayasan Anugrah Kasih Abadi - Friska Crhisti Hutauruk; Fajar Utama Ritonga (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The role of parents for adolescents is very important in shaping the character of adolescents. Teenagers who are in orphanages cannot feel the role of parents because they do not have parents. One way that is done so that teenagers are in care is to accommodate these children into a container, namely an orphanage. The orphanage is one of the child protection institutions that functions to provide protection for the rights of children as representatives of parents in meeting the mental and social needs of foster children so that they have the opportunity to develop themselves until they reach a mature level of maturity and are able to carry out their roles as individuals and groups. citizens in social life. Anugrah Kasih Abadi Foundation Orphanage as a developer in shaping the character of children who are better with the strategies used by the orphanage. The results of the study indicate that the orphanage strategy in shaping the character of the child is by, (1) assigning tasks to foster children, (2) obliging the children to worship. The obstacles encountered in the character building strategy are: (1) The influence of children outside the orphanage, (2) Unruly nature and character.